Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.15376/biores.16.3.5422-5435
|View full text |Cite
|
Sign up to set email alerts
|

Properties of dual-species bamboo-oriented strand boards bonded with phenol formaldehyde adhesive under various compression ratios

Abstract: Physical and mechanical properties were evaluated for bamboo-oriented strand boards (BOSB) prepared with combinations of two contrasting bamboo species and bonded with phenol formaldehyde resin under various compression ratios. The strands from the culms of Gigantochloa pseudoarundinacea and Dendrocalamus asper bamboo were steam-treated at a temperature of 126 °C and a pressure of 0.14 MPa for 1 h and then washed with a 1% NaOH solution. Three-layer dual-species bamboo-oriented strand boards with a shelling ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…This shows that the combination of betung and ampel bamboo strands at different resin content could produce BOSB with a homogeneous density. Inhomogeneous BOSB density will result in different boards' dimensional stability and mechanical strength (Maulana et al 2021d).…”
Section: Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that the combination of betung and ampel bamboo strands at different resin content could produce BOSB with a homogeneous density. Inhomogeneous BOSB density will result in different boards' dimensional stability and mechanical strength (Maulana et al 2021d).…”
Section: Densitymentioning
confidence: 99%
“…8 also shows that mixtures BOSB tends to have a higher IB value than single ampel BOSB but lower than single betung BOSB. This is due to variations of bamboo species density (Maulana 2019;Park et al 2021) that affected the distribution of the adhesive (Febrianto et al 2015(Febrianto et al , 2017Maulana et al 2021d). In general, the IB value of all BOSB in each mixture combination and resin content met the CSA 0437.0 (Grade O-1) standard.…”
Section: Internal Bonding Strengthmentioning
confidence: 99%
“…These indicated that the density of gmelina OSBs is homogeneous. Heterogeneous OSB density could produce varied mechanical strength and dimensional stability of the board (Maulana et al 2021).…”
Section: Densitymentioning
confidence: 99%
“…OSB is made from strands oriented perpendicular to each other between layers and held together using an exterior type adhesive at elevated temperature and high pressure (APA 2017). The quality of OSB is influenced by several factors such as wood species, strand geometry, layer ratio, board density, density profile, extractive substances, pre-treatment, and adhesive type (Adrin et al 2013;Davinsy et al 2019;Febrianto et al 2017;Iswanto et al 2010;Maulana et al 2016Maulana et al , 2020Maulana et al , 2021. Pretreatment is intended to remove extractive substances that can inhibit the gluing process from increasing the adhesive penetration into the strands.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the dimensional stability of BOSB is continually improved to get the result optimally. Steam pretreatment on the bamboo strand followed by sodium hydroxide (NaOH) solution rinsing showed excellent dimensional stability of BOSB (Fatrawana et al 2019;Maulana et al 2019Maulana et al , 2021. This phenomenon is due to the removed hemicellulose and extractive contents from the strands during steaming and washing with a 1% NaOH responsible for the BOSB improved dimensional stability (Fatrawana et al 2019).…”
Section: Introductionmentioning
confidence: 99%